Investigating the scour at piers of successive bridges with debris accumulation - Mahmoud Saleh Al-Khafaji; Layth Abdulameer; Aysar Tuama Al-Awadi; Najah M. L. Al Maimuri; Ahmed N. Al-Dujaili (Journal of Infrastructure Preservation and Resilience)
Abstract Bridge scour around piers and abutments poses a significant threat to bridge stability, particularly in dynamic river environments like the Tigris River in Baghdad. This study aims to investigate the combined effects of successive bridges and debris accumulation on scour depth using HEC-RAS numerical simulations, with a focus on the Al-Sarafiya Bridge. The methodology integrated topographic, hydraulic, and sediment data to develop and calibrate a 1D HEC-RAS model based on a previously conducted study. Six scenarios were analyzed, including single and successive bridges with and without debris, under varying discharge conditions (490 m³/s to 3050 m³/s). The results revealed that an upstream bridge reduces scour depth at downstream piers by 30–40%, highlighting the protective role of hydraulic interactions between successive structures. Debris accumulation significantly increased contraction scour due to flow constriction, with scour depths rising by up to 40.5% under high discharge, but had minimal impact on pier scour, which remained dominated by localized vortices. The study validated HEC-RAS as a reliable tool for scour prediction, with results closely aligning with empirical data. Key findings include: (1) Successive bridges alter flow patterns, reducing downstream pier scour by 30–40%; (2) Debris exacerbates contraction scour but has negligible effects on pier scour; (3) HEC-RAS simulations provided accurate scour depth predictions, supporting its use in bridge design and maintenance. These insights underscore the importance of integrated hydraulic modeling for multi-bridge systems and debris management to mitigate scour risks. The study contributes to safer bridge design in complex river systems, offering practical strategies for long-term stability. Future research should explore debris properties and bridge configurations to refine scour mitigation approaches further.